PERLINDUNGAN HUKUM TERHADAP PENYALAHGUNAAN KARTU KREDIT BAGI NASABAH BANK - Wiguna, I Gusti Ngurah Bagus Adinda; Anom, I Gusti Ngurah (Jurnal Hukum Mahasiswa, 2024)
This study uses a normative legal research method. The main issues discussed focus on the Regulations Concerning Credit Card Misuse for bank customers, credit card misuse often has a significant impact on the victim, a customer experiences loss or theft of a credit card, usually they must immediately report to the bank to block the credit card and prevent further transactions, but the procedure does not always run smoothly, customers are faced with complicated bureaucracy and poor response from the bank. Sometimes customers have to come to the police station to make a report, although in many situations the report does not provide a direct solution to the losses they experience. In Law No. 10 of 1998 concerning amendments to Law No. 07 of 1992 concerning banking, Article 8 of the Law regulates the bank's obligation to provide clear information to customers but is explained in detail. The results of the study on legal protection against credit card misuse for bank customers, explicitly explained that the Banking Law does not directly explain about credit card users but is detailed in the circular letter of Article 28 of the Financial Services Authority Law which regulates credit cards to protect customers and the public by implementing prevention such as providing information and education to the public about the characteristics of the financial services sector, its services and products.